PERAN MEDIA PAPAN MENCOCOKKAN FI`IL MADHI BESERTA DHAMIRNYA DENGAN METODE BERNYANYI UNTUK MELATIH MAHARAH KALAM PADA SISWA - Mukhlisah, Mukhlisah; Maysarah, Maysarah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
This qualitative research, using the analytical description approach, aims to analyze the role of the media in matching a past tense verb and its pronoun with singing methods in training students’ speaking skills. Observations were made by collecting data on the problems faced by students in learning past verbs and pronouns, as well as designing the media to match past verb with pronoun with the method of singing in the process of recognition, pronunciation and comprehension up to the articulation stage. The results of the research were that out of 20 students in the eighth grade of MTS Dar Al-Ihsan, only 5 people understood the past tense verb and its pronoun and could answer correctly. After applying this method, almost all students were able to correctly identify the verb whose use corresponds to the pronoun and were more fluent in pronouncing a past tense verb with the pronoun using the singing method.